Pemanfaatan Bank Sampah Terhadap Perekonomian Masyarakat di Kelurahan Balla Parang Kecamatan Rappocini Kota Makassar - Andi Rifka Putri Dwiyanti R,; Muh. Anwar, (Jurnal Berita Sosial, 2023)
This type of research is a qualitative descriptive study with 5 informants with data collection techniques through observation, interviews and documentation. The data analysis technique starts from the stage of data collection, data reduction, data presentation and then drawing conclusions. The results of the study are: the benefits of waste banks for the community's economy in Balla Parang Village, Rappocini District, Makassar City, including: empowerment in the form of (1) top-down empowerment (2) implementation of waste saving services (3) community participation (4) assistance, monitoring and evaluation. The benefits that are felt by the problem with the existence of this waste bank are (1) increased income of the community as customers (2) customers also get income other than basic income (3) people save waste and exchange it for money (4) create a community that cares about the environment and the environment is clean from garbage.